Molecular Characterization of Multidrug-Resistant Klebsiella pneumoniae Isolated from Some Hospitals in Benghazi, Libya - Elramli , Asma; Almoghraby, Rafeia; Mohamed, Fatma; Ahmed Zaghdani; Asolimany, Sherif; Ameni Arfaoui; Agouri , Siham; Ben Gwirif , Salha; AlQatrani , Aziza; Tayh, Ghassan; Hadda-Imene Ouzari (AlQalam Journal of Medical and Applied Sciences, 2024)
Klebsiella pneumoniae is one of the leading causes of hospital outbreaks worldwide, mainly in hospitalized or immune-compromised individuals. Also, this could be due to the emergence of Multidrug resistance (MDR) Extended Spectrum Beta Lactamase (ESBL) and carbapenemase-producing strains. This study's main goals were to evaluate the prevalence of resistance demonstrated by K. pneumoniae strains found in clinical samples from Benghazi Medical Center and AL-jalaa Hospital and to find evidence of ESBL strains and their resistance to certain antibiotic. During the study period, K. pneumoniae was isolated from 320 clinical samples (urine, sputum, blood and wound). The procedure for processing of samples, identification, susceptibility toward antimicrobials and evidence of ESBL, MBL strains were carried out according to the recommended standards. PCR was used to detect β-Lactamase and carbapenemase resistance genes. From a total K. pneumoniae isolates, 120 (37.5%) were isolated from hospital patients. The isolates exhibited high resistance to all used antibiotics. Forty-eight (40%) of the isolates were ESBL producers. MDR and XDR were identified in 89% and 56% of isolates respectively. ESBL-CTX-M-15 gene and OXA-48 were detected in all isolates. Moreover, SHV and NDM were identified in four isolates. In this study shows the high rate of MDR in clinical K. pneumoniae isolates in hospitals. There is an urgent need to implement an antibiotic resistance surveillance system to regulate and continuously monitor the emergence of antimicrobial resistance. تعتبر الكليبسيلا الرئوية واحدة من اهم البكتيريا المسببة للعدوى داخل المستشفيات في جميع أنحاء العالم، خاصة في المرضى داخل غرف العناية الفائقة أو المرضى الذين يعانون من ضعف المناعة. وتكمن خطورة هذه البكتيريا في مقاومتها للمضادات الحيوية وظهور سلالات مقاومة للأدوية المتعددة (MDR) وانتاجها للانزيمات المقاومة لمجموعة السيفالوسبورينس ومجموعة الكاربابينميESBL ،MBL كان هدف الدراسة هي تقييم مدى انتشار المقاومة التي أظهرتها سلالات الكلبسيلا الرئوية الموجودة في العينات السريرية من مركز بنغازي الطبي ومستشفى الجلاء وإيجاد أدلة على سلالات ESBL وMBL. خلال فترة الدراسة، تم عزل الكلبسيلا الرئوية من 320 عينة سريرية تتضمن البول والبلغم والدم والجروح. تم تعريف هذه العزلات و اختبار هذه السلالات لانتاجها ESBL و MBL وفقًا للمعايير الموصى بها. تم استخدام PCR للكشف عن جينات المقاومة β-Lactamase وcarbapenemase. من مجموع عزلات الكلبسيلا . الرئوية, أظهرت العزلات مقاومة عالية لجميع المضادات الحيوية المستخدمة. ثمانية وأربعون (48٪) من العزلات كانت منتجة لانزيم ESBL. تم التعرف على MDR وXDR في 89% و56% من العزلات على التوالي. تم تحديد وجود جين ESBL-CTX-M-15 وOXA-48 في جميع العزلات. علاوة على ذلك، تم تحديد جين SHV وNDM لبعض العزلات التي تمت دراستها . في هذه الدراسة تبين ارتفاع معدل MDR في عزلات الكليبسيلا الرئوية السريرية في المستشفيات. خطورة انتشار هذه البكتيريا يحتاج الي تنفيذ نظام مراقبة مقاومة المضادات الحيوية لتنظيم ورصد ظهور مقاومة مضادات الميكروبات بشكل مستمر